CONSTRUCTIVIST LESSON PLAN - SHARMA, SANTOSH (THE PRIMARY TEACHER, 2012)
Lesson planning is an important step in effective teaching. Lesson plan reflects a teacher’s philosophy of teaching and learning. The lesson plan guides teachers in selecting and designing learning activities, developing learning materials, organising the class and managing the time. Lesson plan states inputs, interaction during teachinglearning process and expected learning outcomes. Time required, role of teacher, role of students, and plan for assessment of students is also included in the lesson plan. A Lesson Plan has • theme/topic of the lesson; • objectives of the lesson; • time required to complete the lesson; • planned learning activities/tasks; • material required; • engagement of learners with learning tasks (whole class, group work, pair work, individual activity); • scaffolds (Learning support in the form of resource materials, probing questions, suggestions, etc.)